Mulching as soil moisture conservation to improve physiological traits in maize (Zea mays L.) - Zin Mar Aung; Thu Zar (Journal of Agriculture and Applied Biology, 2022)
Field experiments were conducted at Yezin farm and Sepin research farm, Yamethin, Myanmar to study the effect of different mulching materials on percent reduction of soil moisture content and physiological traits in Yezin and Yamethin. Randomized complete block design (RCB) was used with three replications from October, 2019 to March, 2020. Rice straw mulching (T2), rice husk mulching (T3), maize stover mulching (T4), mung bean stover mulching (T5), soybean stover mulching (T6) and white plastic polyethylene mulching (T7) and no mulching (T1) were tested with NK-621, variety. At Yezin, the minimum percent reduction of soil moisture content (45.89) was obtained from T2 and (76.79, 58.07) was resulted in T7 whereas the maximum percent reduction of soil moisture contents (76.93, 89.00, 83.93) were recorded from T1 at 14 DAI (Days after irrigation). At tasseling stage, the maximum photosynthesis rates (20.45 µmol m-2s-1) and (21.59 µmol m-2s-1) were observed from T2 at Yezin and Yamethin. At two locations, the maximum stomatal conductance (158.36 mmol m-2s-1) and (204.44 mmol m-2s-1) was observed from T2 at maximum growth stage. At maximum growth stage, the maximum SPAD values (33.90) and (53.98) were obtained from T6 at Yezin and T2 at Yamethin. The maximum five ears weight (1830.6 g) was recorded from rice straw mulching whereas the minimum five ears weight (1326.0 g) was resulted from no mulching at Yamethin. According to the results, rice straw mulching resulted in the highest physiological traits of maize, and white plastic polyethylene mulching recorded the minimum percent reduction of soil moisture content at Yezin and maize stover mulching at Yamethin.